Education-Based Disaster Mitigation: A Case Study of Coastal Communities Vulnerable to Climate Change - Abdul Wahab Podungge; Dwi Indah Yuliyani Solihin (STKIP Singkawang, 2025)
Disaster mitigation is a crucial aspect in efforts to reduce the risk and impact of disasters that are increasing due to climate change and environmental degradation. However, fragmented mitigation approaches often hamper the effectiveness of policies and community preparedness. Therefore, a holistic strategy is needed that integrates disaster education, community capacity building, and environmental and policy factors to build a more sustainable disaster resilience system. This study aims to analyze the relationship between the three approaches and identify strategies that can be applied to improve community preparedness and resilience to disasters. This study uses a qualitative approach with a case study method to explore the implementation of education-based disaster mitigation in the coastal community of Bone, Bone Bolango Regency. The results showed that the disaster education approach proved effective in increasing individual awareness and skills through community-based learning and integration into the formal curriculum. Increasing community capacity, especially through strengthening social capital, active participation, and utilizing local wisdom, contributed to the effectiveness of community-based mitigation. In addition, the results showed that environmental and policy factors play an important role in supporting disaster resilience. Ineffective regulations and uncontrolled exploitation of natural resources exacerbate disaster risks, requiring policies based on structural and non-structural mitigation. Thus, this study confirms that synergy between education, community capacity, and environmental policies is a strategic step in building a more effective, adaptive, and sustainable disaster mitigation system.